Clinical analysis of 165 cases of erythroderma - Yuan-yuan LI; Dong-wen SHI; Shu-juan SUN; Li-fang SHAO (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To analyze the etiology, triggering factors, clinical characteristics and therapeutic outcomes of erythroderma. Methods: The clinical data of 165 inpatients with erythroderma treated in our department from January 2017 to January 2019 were retrospectively analyzed. Results: These patients included 116 males and 49 females, with mean age of (53.46±18.58) years. Erythroderma secondary to skin disorders, drug allergy and tumors accounted 93.33%, 3.03%, and 1.21%, respectively. The etiologies of the rest cases were unknown. The most common triggering factor was non-standardized use of glucocorticoids. Etiology-based treatment regimens yielded effective rate of 72.73%. Conclusions: Erythroderma occurs mainly in aged males. Psoriasis is the most common cause of erythroderma, followed by eczema. The treatment and prognosis of erythroderma are associated with the primary disease. Etiology-based therapy and symptomatic support can improve the survival rate.